The effect of using individual self-guided Breathing controlled with imagery Training among novice and skill athletes - Roslan, Siti Raihanah (Universiti Sains Malaysia, 2016)
Breathing patterns often get disrupted under stress situations. Trained breathing pattern in individual can have a profound effect on self regulation reducing anxiety, leading to enhanced performance. This study is to determine the effect of using self guided breathing control with imagery training on novice and Netball skilled athletes(SA). The participants were thirteen novices, and thirteen skilled netballers. This study used theSport Imagery Ability Measure (SIAM), Competitive State Anxiety Inventory (CSAI-2R), Rosenberg’s Self-Esteem Scale, breathing rate, and performance scores. The duration of this study is four weeks with twelve sessions of intervention. Imagery training, CSAI-2R, SIAM, self-esteem and control breathing technique done together with researcher in one session every week, and the alternate session were done by participants themselves. Shooting performance and self-efficacy were measured during pre and post test. For the imgery ability, the results showed that all participants scored a moderate to high scores in almost all of the subscales, which is above the minimum point of 25 points out of 100 points. The scores includes visual, speed, emotion, vividness, gustatory, control, olfactory, ease, tactile and duration whereby SA showed greater means score compared to novice netballers. However, the mean score for auditory and kinaesthetic for imagery ability shows greater for novices compared to SA. For self-efficacy (Independent sample r-test) results showed there is no significance difference between two groups, p = 0.268 which is (p > 0.05). Meanwhile self-efficacy (paired /-test), novices showed increase in the mean score from 280.77 to 338.46 yet there is no significance difference with p=0.249. For SA, the mean score change from 370.00during pre-test to 503.85during post-test. It showed significant increased in the self-efficacy for SA from pre-test to post-test withp=0.015. Next, Somatic State Anxiety, both group showed a significance reduction insomatic state within the four weeks of interventions with p=0.026. For selfboth confidence, group showed no significance difference in self-confidence levelwithin four weeks with p=0.621 and for Cognitive State Anxiety, bothgroups shows a significance reduction in cognitive level within four weeks of interventionwith p=0.004.